Exploring science teachers’ self-selection attitudes into professional development programs: motivations, preferences, and implications for practice - Zafar, Faiza; Alston, Christina; Nichol, Carolyn; Tu, Sienna (Frontiers in Education, 2025)
IntroductionProfessional development is essential for science teachers so they can stay current with educational trends, address diverse student needs, and integrate emerging scientific phenomena into their teaching practices. This study explores factors that motivate science teachers to self-select into multi-year-long professional development programs.MethodsThe study’s sample included 14 exemplary science teachers enrolled in multi-year programs and 58 teachers in one-year professional development programs. Quantitative data were collected from all participants using the Basic Psychological Need Satisfaction at Work Scale and qualitative data were gathered from the multi-year program participants through semi-structured interviews.ResultsGrounded in self-determination theory, the quantitative data revealed that exemplary science teachers reported low job satisfaction and significantly lower scores in the relatedness construct, indicating they felt undervalued in their workplaces compared to other participants. Qualitative findings supported these results, as teachers expressed their motivations for participating in multi-year professional development programs driven by a desire for personal growth, continuous learning, and a collaborative learning environment, as well as a lack of rigorous in-school professional development options.RecommendationsThe results inform recommendations for professional development organizers and educational leaders to prioritize offering sustained long-term professional development programs tailored for exemplary teachers so they can feel supported and valued.ConclusionThe study highlights the importance of tailoring professional development programs to the diverse needs of exemplary science teachers such that they feel they belong in the field of science education.